Analisa Efisiensi Tebal Perkerasan Jalan Lingkar Kampus Itera Menggunakan Metode Perancangan Manual Disain Perkerasan (MDP) dan Metode Analisa Komponen - Hermon Frederik Tambunan; Titi Liliani Soedirjo; Rahayu Sulistyorini; Fitria Sari Gunawan (UNIVERSITAS LAMPUNG, 2019)
Road instalation is one of crucial sector which become connection zones of campus ITERA. Optimum planning of design pavement is very necessery. Variable that affected the planning process of pavement design on the road zone of ITERA is, CBR Subgrade value, Traffic loads factor, road classification, and pavement types. Pavement design of ringroad inside campus ITERA planned with 2 methods, the pavement thickness analysis method using Bina Marga 1987 and Pavement Design Manual using Bina Marga 2013. Based of survey and analysis obtained CBR subgrade with 6%-10%, traffic loads for 20Years reach 1.210.994, and region condition categorized as tropical climate with rainfall around 1900-2500mm/year. Pavement design with the pavement thickness analysis method using Bina Marga 1987 and Pavement Design Manual using Bina Marga 2013 resulted variation thickness, MDP2013 with flexible pavemet HRS WC, HRS Base, LPA class A and LPA class B resulted total thickness at 44cm while MAK1987 resulted at 35cm. Significant differences is in LPA class A and LPA class B. By the studies, total thickness with the pavement design manual 2013 is more thick than using the pavement thickness analysis using Bina Marga 1987, this caused by some standard in the pavement design manual 2013.